Development of a methodology to demonstrate the environmental impact of connected vehicles under lane-changing conditions. (August 2013) - Choi, Ji-Eun; Bae, Sang-Hoon
This paper describes a lane-change model for connected vehicles, and evaluates the environmental impact per road level of service (LOS) when a host vehicle makes a lane change. During manual driving, the host vehicle accelerates or decelerates to create a safe distance before the vehicle makes a lane change. During automated driving, however, the host vehicle makes lane changes in response to the acceleration or deceleration of the vehicle in front of it through vehicle-to-vehicle communications. The gap, safe distance, and variation in vehicle speed depending on the LOS are analyzed using simulation for both automated and manual driving. For lane changing from a faster to a slower lane, the reduction in CO2 emissions of the connected vehicle was in the range 4770–54, 291 g/km in comparison to the manual vehicle. For lane changing from a slower to a faster lane, the CO2 reductions were in the range 40, 788–91, 884 g/km. In more complex traffic situations, the CO2 reductions of the connected vehicles were larger than in simple traffic situations. This study indicates that the use of connected vehicles can result in a reduction of CO2 emissions.